Education on Visa Extension Digitally Via Online - Nuning Indah Pratiwi; I Made Hendra Putra Yasa; Wahyu Indra Satria (LPPM UIKA Bogor, 2024)
Education in Visa Extension Digitally Via Online to facilitate the process of making and extending a visa, the method used includes direct assistance, assistance itself, which is a method in which a teacher or mentor is actively involved in the learning or training process by working with participants in a real situation or a relevant environment. This assistance can include mentoring, hands-on practice, or joint work situations. The aim is to enable trainees to learn by involving themselves in tasks or situations appropriate to their field of study. There is a data discrepancy. Visa extensions can be done by visiting the office in person or by yourself online through the website, of course with their respective rules. Technology spoils us in this regard and that is also felt by the consumers of PT. Smart Visa Bali. Through the website, we can register directly without having to go to the office and of course, also save on vehicle costs.